Legal Support of Economic Mechanism of Groundwater Protection and Use Regulation in Central Asia Region - BORODINA, Alina; YERKINBAYEVA, Lazzat K. (Journal of Advanced Research in Law and Economics; Vol 8 No 3 (2017): JARLE Volume VIII Issue 3(25) Summer 2017, 2017)
Groundwater is one of the main sources of fresh drinking water, a lack of which we begin to feel acutely. Water resources are distributed unevenly. This exacerbates the problem of drinking water scarcity. This situation requires legislative groundwater regulation. This paper discusses some problems of legal support of economic mechanism of groundwater protection and use regulation in Kazakhstan as a state that has a deficit of water resources. To achieve this goal we have conducted a comparative legal analysis of the legislation of Kazakhstan in the field of water resources management. It has studied the features of groundwater as an object of legal regulation. Economic instruments, regulating the protection and use of groundwater, have been investigated and the ways of legislation improvement were suggested in this paper as well. The proposed amendments to the legislation are oriented to increasing funding for groundwater protection and use.